Can Consumer Citizenship Behavior be Created Using Service Robots in Luxury Hospitality Services? - Agrawal, Gautam; Sodhi, Savita; Mohapatra, Amiya Kumar; Bhandari, Krishna Raj (Indian Journal of Marketing, 2023)
Purpose : This study sought to increase an understanding of consumer citizenship behavior through the service quality of AI-mediated service robots (SR) in the luxury hotel context. Since the expectations and demands from luxury customers are different, this paper studied the effect of service quality provided by robots on customer citizenship behavior. Methodology : In the initial phase, qualitative research was conducted by interviewing people who had experienced SR in luxury hospitality settings. The second phase of the study was conducted based on the respondents’ themes. In the second phase, video clips of robots performing tasks like concierge and front-desk employees were shown to understand the customers’ perceptions. Findings : The study’s findings showcased the importance of communication quality between the inorganic service agent and humans. Simultaneously, the factors like problem-solving and trendiness did not have a positive impact on service quality. However, an interesting finding was that the perception of robot service quality positively affected consumer citizenship behavior in the luxury hotel context. Practical Implications : Luxury hotels have deployed SR in their operations in developed economies. Luxury hotels are renowned for their service quality, and by deploying SR, they are entering a new service industry domain. The results of this study showcased that communication ability, competence, and quality are significant factors in perceiving high-service quality by luxury consumers. Originality/Value : The research explored the impact of service robots in the luxury hospitality industry on consumer citizenship behavior toward the hospitality organization. The study empirically validated the essential factors for creating citizenship behavior among luxury patrons.